Sistem Dewatering Air Panas Tambang Bawah Tanah Toguraci PT. Nusa Halmahera Minerals - Suroto, Jimmy Bob; Rabbani, Ramdhan; Latif, Anas Abdul; Aesh, Presentia Biserva (PERHAPI, 2018)
The development of the Toguraci Underground Mine was begun in 2011 with the ore production started in 2012. The amount of water continued to increase in the Underground Mine at the beginning of 2014 which became problem that effected the activities of mining. The increase of hot water Toguraci underground mining effected to the safety for workers who are exposed to hot water, ventilation problems and equipment that are submerged in hot water. Tuguraci mine has two dewatering systems, namely dewatering systems on the surface and dewatering systems in underground mines. The handling of surface water comes from pumping underground to surface where water discharge is around 400 L / s with the temperatures ranging from 70Â°C while water treatment in underground mines includes decreasing water heading levels and pumping water from underground mines to the surface. The increase water entering heading development and stoping can be overcome by changing the surface dewatering system by using water cooling, while underground mining is done by changing the pipeline from the polypipe to the steel pipe and to reduce water entering the mining front is doned by drill holes for installing submersible pumps and replacing Oddesse pump to the Schlumberger pump which is more resistant to high temperature hot water, as long as mining operations take place 48 borehole drilling has been done with 11 borehole flowrate below 5 l / s and 37 borehole with flow rate above 5 l / s, and a water drop of around 77 meters